An analysis on the challenges and dynamics to the challenges to synergies for subregional peace support missions : a case of the Southern African Development Cooperation (SADC) and the International Conference on the Great Lakes region (ICGLR) in the Eastern DRC recurring conflict - Chereni, Valerie Mwanashe Florence (Midlands State University, 2020)
This study takes a look at the complexity of the recurring conflict in Eastern DRC and the efforts put in place by the sub regional organizations particularly the SADC and ICGLR in trying to achieve sustainable peace in the war torn region of the Congo. Peace support operations in the 21st century has been undertaken at the multilateral, regional and sub-regional levels in given conflicts by a range of actors. Scholarly questions have been asked the effectiveness of these operations citing the failure to achieve sustainable peace in the war zones. It therefore concerns scholars on the challenges that these efforts are facing which are delaying progress on achieving the desired sustainable peace in the conflict areas. In the case of this study, which focuses on the SADC and ICGLR synergies for peace support in the DRC, questions have been centered on the following: What are the challenges to sub regional synergies in peace support operations? What are the dynamics surrounding the challenges to sub regional synergies in peace support operations in Eastern Congo? These aspects which are necessary in designing effective approaches to the synchronized efforts for peace support where analyzed and recommendations for effective strategy that applies in the context were also given. In trying to answer the key questions this study uses qualitative approaches in collecting and analyzing data not only from primary and secondary sources, but also from interviews conducted. Thus the findings of this research were analyzed within the framework of the core objectives of the study which seeks to root out the challenges of sub regional synergies for peace support operations in the recurring Eastern DRC Conflict looking at the efforts by the ICGLR and the SADC regional blocs as well as mapping out recommendations tailor made for the specific context of conflict so that future peace support efforts will reap sustainable peace in the Eastern Region of the Congo. The Study therefore seeks to offer policy and strategy suggestions on the execution of future synchronized peace support operations in Eastern DRC recurring conflict. The theoretical concepts of New Institutionalism and Conflict Transformation were used as tools of analysis as they prove a fundamental conceptual link for sustainable results of peace support operations. Whilst existing literature provides universal challenges to the efforts to peace support, this paper makes focus on the interventions of SADC and ICGLR in DRC to identify the challenges that are delaying progress towards sustainable peace politically, socially and economically and also looking into the dynamics of these challenges as well as giving tailor made recommendations fit to address the case in question such as the removal of bias and putting efforts to ensure inter cultural competence development especially in the Eastern Region and greater part of the great lakes region.